Identificación de impactos ambientales y sociales generados a la seguridad alimentaria en Colombia a causa de la producción de biodiesel. (2023)
The purpose of this monograph is to analyze the socio-environmental impacts that the production of biofuels has on food security in Colombia. To begin, a broad review of bibliographies will be carried out that will make it possible to reveal the social and environmental consequences that it has generated. the planting of these energy crops in different regions of the country, forced displacements, social conflicts over land ownership and finally a detailed analysis of the impact on food security taking into account the Colombian regulatory framework. This bibliographic review made it possible to make visible that although energy crops have a large number of environmental benefits such as reduction of greenhouse gas emissions, less energy dependence on fossil fuels, they also have negative collateral effects such as the impact on agricultural and livestock production. which many families in the country depend on for their food, a situation that is aggravated by the acquisition of land for this purpose, affecting rural communities to finally show whether the positive impacts of the use of alternative energies such as agricultural development, job creation and contribution to energy security, offset the social effects it has generated.